Fetch. Book one, The journey - Sizemore, Mike (Graphic novelist); Carpenter, John, 1948-; King, Sandy, 1952- (John Carpenter presents Storm kids., 2023)
"Danni is twelve years old and struggling to get over the loss of her dog, Pirate, when a new teacher and an old school book reveal to her the world of Greek mythology. Danni stumbles across an illustration that looks familiar enough for her to leave the house in the dead of night and seek out what she thinks could be the gate to Hades, the Greek Underworld, and perhaps a way to bring her dog back to the land of the living. What she didn't expect was her younger brother, Sammy, to tag along or that once in the Underworld she'd need a guide... and two 21st century kids on a quest to save their dead dog was the last thing Odysseus was expecting. Adventuring in the Underworld since the fall of Troy he's the last of his kind - a true Hero - but with enemies leaping on them at every turn and monsters and gods to overcome this may be his toughest odyssey yet!"--Amazon.